Case Report: Rare aplastic anemia in pediatric systemic lupus erythematosus: a case series and systematic literature review - Gao, Xianfei; Li, Ying; Lan, Xuerong; Zeng, Ping (Frontiers in Pediatrics, 2025)
BackgroundSystemic lupus erythematosus (SLE) is a complex autoimmune disease in which the immune system mistakenly attacks healthy cells and tissues. This condition can impact various organs and systems, including the hematological system, where aplastic anemia (AA) emerges as a particularly severe and rare complication. Relevant clinical manifestations and treatment experiences must be shared and updated urgently.MethodsThis manuscript presents the clinical features, examination, and treatment of two pediatric SLE patients with AA. And a systemic search of MEDLINE, EMBASE, LILACS, SciELO, and Scopus, using MeSH headings and keywords for “Aplastic Anaemia” and “Systemic Lupus Erythematosus”.ResultsBoth of our cases were severe, resulting in one death. Our systematic literature review identified 32 eligible studies. We found a total of 38 patients, and along with the two patients from our case series, there were 9 out of 40 SLE patients who experienced alopecia areata as children. In all 40 patients, 52% (21 out of 40) developed AA at the onset of SLE. The infection rate was concerning, with 16 out of 40 patients affected. While 83% (33 out of 40) of the patients showed improved outcomes, all seven patients who died had contracted an infection.ConclusionSLE with AA is rare in both children and adults. Although the prognosis of this dangerous disease is optimistic in terms of data, it is still necessary to be vigilant, and early bone marrow examination, infection prevention, and on-time treatment are crucial.